Pengaruh Faktor Eksternal Terhadap Strategi Pemasaran Pada Mcdonald’s - Adi Neka Fatyandri; Febbryan Zhangrinto; Hendro Hendro; Katherine Katherine; Nancy Nancy; Steven Steven (Universitas 17 Agustus 1945 Semarang, 2023)
Consumer interest in McDonald's, which is operated as a franchise, remains high in Indonesia and elsewhere. McDonald's is one of the franchises that has expanded the most both in Indonesia and internationally. The term